Comparison of phenotype, comorbidities, therapy and adverse events between psoriatic patients with and without psoriatic arthritis. Biobadaderm registry. (12th April 2017) - Pérez‐Plaza, A.; Carretero, G.; Ferrandiz, C.; Vanaclocha, F.; Gómez‐García, F.J.; Herrera‐Ceballos, E.; De la Cueva‐Dobao, P.; Belinchón, I.; Sánchez‐Carazo, J.L.; Alsina, M.; López‐Estebaranz, J.L.; Ferrán, M.; et al.
Abstract: Background: There are a limited number of studies comparing psoriasis patients without psoriatic arthritis (PsA) to those with arthritis. Previous results are controversial. Objectives: To perform a comparative analysis of the phenotype, baseline comorbidities, therapeutic profile and incidence of adverse events (particularly overall adverse events, infections and infestations, malignancies and psychiatric disorders) among psoriatic patients with/without PsA. Methods: All the patients on the Biobadaderm registry, a prospective inception cohort of psoriasis patients on systemic therapy, were included. Patients were divided into two groups: those with psoriasis without arthritis at the time of entry into the cohort (Pso group) and those with psoriasis and psoriatic arthritis (PsA group) at entry. Patients were followed until the censorship date (last visit in a lost‐to‐follow‐up patient, or 10 November 2015, whichever occurred first). We excluded all the patients who developed any kind of signs and/or symptoms of joint involvement during the follow‐up. A descriptive analysis was performed. We estimated incidence ratios (IRR) of adverse events during systemic treatment using a mixed‐effects Poisson regression. Results: We included 2120 patients: 1871 (88%) patients with psoriasis without arthritis and 249 (12%) with psoriasis and PsA. The follow‐up time was 5020 patients‐year in the Pso group and 762 patients‐year in the PsA group. Patients with PsA had more comorbidities, particularly hypertension and liver disease; used a higher number of systemic therapies, particularly anti‐TNFα drugs and combination therapy; and presented more adverse events (IRR adjusted = 1.29; 95% CI: [1.05–1.58]), particularly serious adverse events (IRR adjusted = 1.51; 95% CI: [1.01–2.26]) and infections/infestations (IRR adjusted = 1.88; 95% CI: [1.27–2.79]), independently of the associated comorbidities and present/past therapies. Conclusions: Given the differences between patients with psoriasis alone or with psoriasis associated with PsA, patients with psoriasis and PsA should be followed and managed more closely and with specific attention.